Probabilistic reference and grounding with PRAGR for dialogues with robots. Issue 5 (2nd September 2016) - Mast, Vivien; Falomir, Zoe; Wolter, Diedrich
Abstract : In this paper, we present a system for effective referential human–robot communication in the face of perceptual deviation using theP robabilisticR eferenceA ndGR ounding mechanism PRAGR and vague feature models based on prototypes. PRAGR can handle descriptions of arbitrary complexity including spatial relations and uses flexible concept assignment in generation and resolution of referring expressions for bridging conceptual gaps in referential robot–robot or human–robot interaction. We evaluate the benefit of using vague as compared to crisp properties regarding referential success and robustness towards perspective alignment error in referential robot–robot and human–robot communication.